Effects of all‐trans retinoic acid (ATRA) in addition to chemotherapy for adults with acute myeloid leukaemia (AML) (non‐acute promyelocytic leukaemia (non‐APL)) - Küley‐Bagheri, Yasemin (Cochrane Database Syst Rev, 2018)
BACKGROUND: Acute myeloid leukaemia (AML) is the most common acute leukaemia affecting adults. Most patients diagnosed with AML are at advanced age and present with co‐morbidities, so that intensive therapy such as stem cell transplantation (SCT) is impossible to provide or is accompanied by high risks for serious adverse events and treatment‐related mortality. Especially for these patients, it is necessary to find out whether all‐trans retinoic acid (ATRA), an intermediate of vitamin A inducing terminal differentiation of leukaemic cell lines, added to chemotherapy confers increased benefit or harm when compared with the same chemotherapy alone. OBJECTIVES: This review aims to determine benefits and harms of ATRA in addition to chemotherapy compared to chemotherapy alone for adults with AML (not those with acute promyelocytic leukaemia (non‐APL)). SEARCH METHODS: We searched the Central Register of Controlled Trials (CENTRAL), MEDLINE, study registries and relevant conference proceedings up to July 2018 for randomised controlled trials (RCTs). We also contacted experts for unpublished data. SELECTION CRITERIA: We included RCTs comparing chemotherapy alone with chemotherapy plus ATRA in patients with all stages of AML. We excluded trials if less than 80% of participants were adults or participants with AML, and if no subgroup data were available. Patients with myelodysplastic syndrome (MDS) were included, if they had a refractory anaemia and more than 20% of blasts. DATA COLLECTION AND ANALYSIS: Two review authors independently extracted data and assessed the quality of trials. We contacted study authors to obtain missing information. We used hazard ratios (HR) for overall survival (OS) and disease‐free survival (DFS; instead of the pre‐planned event‐free survival, as this outcome was not reported), and we calculated risk ratios (RR) for the other outcomes quality of life, on‐study mortality and adverse events. We presented all measures with 95% confidence intervals (CIs). We assessed the certainty of evidence using GRADE methods. MAIN RESULTS: Our search resulted in 2192 potentially relevant references, of which we included eight trials with 28 publications assessing 3998 patients. Overall, we judged the potential risk of bias of the eight included trials as moderate. Two of eight trials were published as abstracts only. All the included trials used different chemotherapy schedules and one trial only evaluated the effect of the hypomethylating agent decitabine, a drug know to affect epigenetics, in combination with ATRA. The addition of ATRA to chemotherapy resulted in probably little or no difference in OS compared to chemotherapy only (2985 participants; HR 0.94 (95% confidence interval (CI) 0.87 to 1.02); moderate‐certainty evidence). Based on a mortality rate at 24 months of 70% with chemotherapy alone, the mortality rate with chemotherapy plus ATRA was 68% (95% CI 65% to 71%). For DFS, complete response rate (CRR) and on‐study mortality there was probably little or no difference between treatment groups (DFS: 1258 participants, HR 0.99, 95% CI 0.87 to 1.12; CRR: 3081 participants, RR 1.02, 95% CI 0.96 to 1.09; on‐study mortality: 2839 participants, RR 1.02, 95% CI 0.81 to 1.30, all moderate‐certainty evidence). Three trials with 1428 participants reported the adverse events 'infection' and 'cardiac toxicity': There was probably no, or little difference in terms of infection rate between participants receiving ATRA or not (RR 1.05, 95% CI 0.96 to 1.15; moderate‐certainty evidence). We are uncertain whether ATRA decreases cardiac toxicity (RR 0.46, 95% CI 0.24 to 0.90; P = 0.02, very low certainty‐evidence, however, cardiac toxicity was low).    Rates and severity of diarrhoea and nausea/vomiting were assessed in two trials with 337 patients and we are uncertain whether there is a difference between treatment arms (diarrhoea: RR 2.19, 95% CI 1.07 to 4.47; nausea/vomiting: RR 1.46, 95% CI 0.75 to 2.85; both very low‐certainty evidence). Quality of life was not reported by any of the included trials. AUTHORS' CONCLUSIONS: We found no evidence for a difference between participants receiving ATRA in addition to chemotherapy or chemotherapy only for the outcome OS. Regarding DFS, CRR and on‐study mortality, there is probably no evidence for a difference between treatment groups. Currently, it seems the risk of adverse events are comparable to chemotherapy only. As quality of life has not been evaluated in any of the included trials, further research is needed to clarify the effect of ATRA on quality of life.